Ludwig's Angina in a 6-Year Child: Case Report - Akbari, Negarin; Razavi, Ali; Sabzi, Zahra; Parhiz, Jabbar (Wiley, 2025)
Ludwig's angina is a rare but potentially fatal cellulitis that affects the submandibular, sublingual, and submental spaces, typically triggered by dental infections. This case report details a severe presentation of Ludwig's angina in a 6-year-old girl who presented with submandibular swelling, fever, voice alterations, and respiratory distress. Diagnosis was based on clinical evaluation, supported by CT imaging, revealing significant airway narrowing and lymphadenopathy. The patient was promptly intubated to secure the airway, followed by emergency surgical drainage and intravenous antibiotics. Postoperative care included sedation, ongoing monitoring in the PICU, and close follow-up by multiple specialties. After a 10-day hospitalization, the patient showed significant recovery with no complications. The case underscores the importance of early diagnosis and intervention in preventing severe complications such as airway obstruction, sepsis, and mediastinal spread. It highlights the critical role of interdisciplinary collaboration, including pediatric infectious disease specialists, surgeons, and anesthesiologists, in managing this life-threatening condition effectively.
Keywords: Antibiotic Therapy; Case Report; Child; Ludwig's Angina; Submandibular Gland